2019
DOI: 10.1039/c9ra08245j
|View full text |Cite
|
Sign up to set email alerts
|

A Maitake (Grifola frondosa) polysaccharide ameliorates Alzheimer's disease-like pathology and cognitive impairments by enhancing microglial amyloid-β clearance

Abstract: PGM ameliorates AD-like pathology and cognitive impairments by enhancing microglial amyloid-β clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…A Maitake-derived polysaccharide called proteo-β-glucan (PGM), was reported to be a strong immunomodulator [26]. However, it remained uncertain if this polysaccharide could have immunomodulatory and neuroprotective effects on transgenic APP/PS1 mice, a common model for AD [26]. This study showed PGM-enhanced learning and memory, with reduced histopathological irregularities and neuronal loss in APP/PS1 mice [26].…”
Section: Antioxidant Activity Of Polysaccharidesmentioning
confidence: 84%
See 3 more Smart Citations
“…A Maitake-derived polysaccharide called proteo-β-glucan (PGM), was reported to be a strong immunomodulator [26]. However, it remained uncertain if this polysaccharide could have immunomodulatory and neuroprotective effects on transgenic APP/PS1 mice, a common model for AD [26]. This study showed PGM-enhanced learning and memory, with reduced histopathological irregularities and neuronal loss in APP/PS1 mice [26].…”
Section: Antioxidant Activity Of Polysaccharidesmentioning
confidence: 84%
“…According to Bai et al [26] the edible and curative mushroom, Maitake, is highly nutritious and contains a large amount of biologically active and health-promoting compounds [26]. A Maitake-derived polysaccharide called proteo-β-glucan (PGM), was reported to be a strong immunomodulator [26].…”
Section: Antioxidant Activity Of Polysaccharidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Various kinds of polysaccharides reportedly have memory-improving activity against various animal models, such as those with amyloid b- and scopolamine-induced memory impairment [ 36 , 37 , 38 , 39 ]. It is generally believed that only some small molecules can cross the blood–brain barrier (BBB) via lipid mediation.…”
Section: Discussionmentioning
confidence: 99%